PENGENALAN METODE VAMELA THE ANESTHESIA (HYPNOSIS ANESTHESIA METHOD VACCINE) SEBAGAI ALTERNATIF ANESTESI YANG AMAN DAN EFEKTIF - Syaeful Islam (Kalam Nusantara Institute, 2023)
Hypnotherapy or clinical hypnosis is a mind therapy and healing technique that useshypnosis methods to give positive suggestions or commands to the subconscious mind to curea psychological disorder or to change thoughts, feelings and behavior for the better. Hypnosisis not like other ways of treating the symptoms or effects that appear. By eliminating the cause,the consequences will automatically disappear or be cured (Ratna, 2017). Case in point, forexample, treatment of anxiety. Anxiety that occurs without any external reason and begins toaffect human daily functioning, mental health professionals view it as a psychological problemcalled anxiety disorder.Previously, in the working area of the Pajarakan Health Center, many patients, rangingfrom children, adolescents, adults and even the elderly, were afraid of needles during the Covid-19 vaccination activities or complete basic immunization. Then the Pajarakan Health Centerbegan to take action and began to collect data to carry out problem-solving analysis also throughcoordination efforts with cross-programs and cross-sectors so that an activity